Survival and Sprouts Production of Prickly Pear (Opuntia ficus-indica) Using Minimal Fractions - Solano, Jaime; Orihuela, Agustín (Journal of the Professional Association for Cactus Development, 2008)
To reduce the cost of establishment of new plantations of Opuntia ficus-indica in marginal rural zones in Mexico, four treatments were established according to the proportion of the cladode used as germinal material: T1=plantation of a whole cladode (1/1), T2=half cladode (1/2), T3=a quarter cladode (1/4), and T4=an eighth cladode (1/8). Survival rate was estimated at five and eight months after plantation, which presented different (P<0.05) values for T1 and T2 with respect to T3 and T4 (100% and 98.6% vs 67.3% and 57.3%, respectively). The percentage of plants with one sprout five months after plantation was greater (P<0.05) in T1 with respect to the other treatments (42.6% vs 18.6%, 24.0% and 5.3% for T1, T2, T3, and T4, respectively). Nevertheless, at eight months of age, T2 showed higher (P<0.05) incidence of sprouts (42.6%), with similar values of those observed in T1 three months before. The percentage of plants with two or more sprouts at five and eight months after plantation was different (P<0.05) 24% and 91.3%, respectively, for T1 with respect to all other treatments. The weight of the sprouts at five and eight months favored T1 (P<0.05) in comparison with all other treatments (39.1 ±6.4 g and 195.8 ±12.8 g, respectively). It is concluded that the use of half cladodes in the establishment of this cultivation does not affect the survival rate of the material planted. Although production (in number and weight of sprouts) is delayed more than three months, using half cladodes represents 50% saving in vegetative material at the time of plantation in comparison with the traditional method.